The protection of indigenous people’s rights in the equitable management of water resources - Maramis, Meylan Maasye; Budiono, Abdul Rachmad; Djatmika, Prija; Safa’at, Rachmad (Technium Social Sciences Journal, 2021)
Local wisdom plays an important role in the management of water resources and the environment. However, local wisdom in managing water resources and the environment cannot be separated from various challenges. The concept of a local environmental wisdom system is rooted in the knowledge and management system of indigenous peoples through a long process of interaction and adaptation of the environment and natural resources. Indigenous peoples are able to develop ways to sustain life by creating value systems, patterns of life, institutional systems, and laws that are in harmony with condition and availability of natural resources around the area where they live. This study aims to determine the condition of water resources, the role of indigenous peoples in preserving and conserving water resources, the values of local wisdom, and preserving the values of local wisdom in maintaining the conservation of water resources. Local wisdom in maintaining the conservation of water resources in the regulation of Law No. 17 of 2019 concerning water resources regulates indigenous peoples in water resources management. This writing is structured using a normative juridical writing method with a conceptual and analytical approach.